2020
DOI: 10.1002/dvg.23399
|View full text |Cite
|
Sign up to set email alerts
|

The plastic genome: The impact of transposable elements on gene functionality and genomic structural variations

Abstract: Transposable elements (TEs) are DNA sequences that can change their position within genomes. TEs are present in most organisms and can be an important genomic component. Their activities are manifold: restructuring of genome size, chromosomal rearrangements, induction of gene mutations, and alteration of gene activity by insertion near or within promoters, intronic regions, or enhancer. There are several examples of mutations and other genetic variations determined by the activity of TEs, associated with the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 297 publications
(504 reference statements)
0
14
0
1
Order By: Relevance
“…In plants and animals, different forms of stress are known to act as triggers or facilitators of TE mobility [140,141]. Several studies in plants have reported overexpression of TEs following abiotic or biotic stress conditions such as temperature, nitrate de-privation, and wounding [142][143][144][145]. Activation of TEs in response to different stresses has also been demonstrated in insects [146], and especially in the context of insecticide resistance [147][148][149].…”
Section: Role Of Stress and Environmental Pollution In Te Mobility An...mentioning
confidence: 99%
“…In plants and animals, different forms of stress are known to act as triggers or facilitators of TE mobility [140,141]. Several studies in plants have reported overexpression of TEs following abiotic or biotic stress conditions such as temperature, nitrate de-privation, and wounding [142][143][144][145]. Activation of TEs in response to different stresses has also been demonstrated in insects [146], and especially in the context of insecticide resistance [147][148][149].…”
Section: Role Of Stress and Environmental Pollution In Te Mobility An...mentioning
confidence: 99%
“…Significantly, active transposable elements can increase the size of the genome and facilitate rapid genetic adaptation to stressful environments [88]. Transposition activity can have positive and negative influences on gene expression and strong promoters from viruses and transposable elements contribute to the rapid genetic diversity of primates [89] and many plant species [90,91]. It is also of note that stable and conserved G-quadruplexes are located in the long terminal repeat (LTR) promoter of retroviruses [92] and human herpesviruses immediate-early promoters [58].…”
Section: Evolutionary Pressure For Promoter Diversitymentioning
confidence: 99%
“…Not only has the human genome evolved in relation to its symbiotic microorganisms (and vice versa), but important portions of the human genome are made up of viral vestiges. From exogenous elements, these components have become integral parts of the genome, modifying its functionality and expressive possibilities [14,15,21,22,25,26,28,29,32,33].…”
Section: A Wider Different Lookmentioning
confidence: 99%